Isolation and characterization of mesenchymal stem/stromal cells from Ctenomys minutus - Pereira, Mayra Ramos de Jesus (2018)
Mesenchymal stem/stromal cells (MSCs) are multipotent cells distributed in all tissues and characterized by adherence, morphology, immunophenotype and trilineage differentiation potential. The present study aimed to isolate and characterize adherent MSC-like populations from different tissues of Ctenomys minutus, a threatened wildlife rodent popularly known as tuco-tuco. Adherent cells were isolated from bone marrow, brain, liver, pancreas and adipose tissue of three adult animals collect in southern Brazil. Cultures showed typical morphology and proliferation potential. Adipose-derived MSCs showed trilineage potential. Cultures derived from adipose tissue, bone marrow and brain were immunophenotyped with negative results for CD31, CD44, CD45, CD106, and MHC class II, as well as strong positive results for CD29. Low fluorescence levels were seen for CD49d, CD90.2 and CD117. Cultures were negative for CD49e, except for brain-derived cultures that were weakly positive. CD11b was negative in adipose-derived MSCs, but positive in brain and bone marrow-derived cultures. The scratch assay showed high migration potential for pancreas and adipose tissue-derived cells. This study represents the first report of isolation and characterization of cultures having characteristics of MSCs from Ctenomys minutus. The collection of biological information for biobanks represents an important contribution to the creation of strategies for prevention of loss of genetic diversity.